Three-Dimensional Microfabrication Using Two-Photon Polymerization - Fundamentals, Technology, and Applications - Baldacchini, Tommaso (Elsevier, 2016)
This book is the first comprehensive guide to TPP microfabrication-essential reading for researchers and engineers in areas where miniaturization of complex structures is key, such as in the optics, microelectronics, and medical device industries.TPP stands out among microfabrication techniques because of its versatility, low costs, and straightforward chemistry. TPP microfabrication attracts increasing attention among researchers and is increasingly employed in a range of industries where miniaturization of complex structures is crucial: metamaterials, plasmonics, tissue engineering, and microfluidics, for example.The guide covers all aspects of TPP, including the pros and cons of TPP microfabrication compared to other techniques, as well as practical information on material selection, equipment, processes, and characterization.